Family Based Education in Prevention of Anemia In Pregnant Women in Bandar Khalifah Village Percut Sei Tuan: Pendidikan Berbasis Keluarga Dalam Pencegahan Anemia Pada Ibu Hamil di Desa Bandar Khalifah Percut Sei Tuan - Susanti Pasaribu, Riska; Natalia Sinuhaji, Lidya; Ridesman, Ridesman; Simamora, Lasria; Suci Triana Ginting, Siska; Simbolon, Marlina (Jukeshum: Jurnal Pengabdian Masyarakat, 2025)
Cases of anemia caused by malnutrition, especially iron deficiency anemia, reach 75%. The prevalence of iron and other micronutrient deficiencies is a serious problem in developing countries. The incidence of anemia or lack of blood among pregnant women in Indonesia is still relatively high, at 48.9%. Anemia is closely related to malnutrition, which is a multifactorial influence and interaction between food intake and frequency of infection. The prevalence of anemia among pregnant women at the Bandar Kalipah Community Health Center was recorded at 24.9%. The community service method applied in this activity directly involves families in efforts to reduce the incidence of anemia in pregnant women, through lectures, counseling, discussions, and training. As an initial step, a pre-test and post-test analysis was carried out to measure family knowledge about anemia, in order to ensure an increase in family knowledge and participation in efforts to prevent anemia. The knowledge of pregnant women's families before (pre-test) and after (post-test) being given education on preventing anemia through family-based education showed good results, with a percentage of good knowledge of 23.29% in the pre-test and increasing to 92.0% in the post-test. Sufficient knowledge was recorded at 24.70%, while low knowledge decreased to 3.00%. This activity aims to provide education to families who accompany pregnant women and is carried out repeatedly and consistently in Bandar Khalifah Village, where pregnant women must be accompanied by their families during pregnancy check-ups. This activity was carried out in October 2024 by providing education on the causes of anemia, the process of anemia, prevention of anemia, and proper treatment for anemia. With this activity, there was an increase in knowledge, attitudes, and experience for families of pregnant women in efforts to prevent anemia.